Żywotność korzeni w wierzchnich warstwach gleby w drzewostanach sosnowych w 10 lat po trzebieży - Farfał, Dorota (Leśne Prace Badawcze, 2010)
The vitality of roots in the soil at depths of 0–5 cm and 5–15 cm was determined for pine stands which had been thinned ten years earlier using various different methods and means of timber harvest. The parameters adopted to assess root vitality were: total root density (g/100 cm 3 of soil) and fractional root density divided into live and dead root diameters for individual tree species. Overall, live roots were most prevalent (88–96%) in the investigated stands. Whereas, the total density of dead roots was 0.033–0.111 g/100 cm 3 of soil at 0-5 cm depth and 0.039–0.058 g/100 cm 3 of the soil at 5–15 cm depth. The opening of the canopy in older stands caused more-intense development of fine roots in the plants of the forest floor (0.411–0.567 g/100 cm 3 of soil) compared to the fine roots of pine trees (0.145–0.177 g/ 100 cm 3 of soil), especially at 0–5 cm soil depth. The studies did not reveal significant differences in root development on the old skidding roads due to variation in the methods of timber harvesting during thinning operations ten years earlier nor when compared with the control plots.